2012
DOI: 10.1111/j.1464-410x.2012.11278.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil promotes neuroprotection of the pelvic ganglia neurones after bilateral cavernosal nerve resection in the rat

Abstract: Objectives To determine the gene expression profile of pelvic ganglia neurones after bilateral cavernosal nerve resection (BCNR) and subsequent treatment with sildenafil in relation to neurotrophic-related pathways. Materials and methods Fisher rats aged 5 months were subjected to BCNR or sham operation and treated with or without sildenafil (20 mg/kg body-weight in drinking water) for 7 days. Total RNA isolated from pelvic ganglia was subjected to reverse transcription and then to quantitative rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…BCNR was performed as we previously described [25,26,42,43]. In the sham-operated group both cavernosal nerves were identified but not resected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCNR was performed as we previously described [25,26,42,43]. In the sham-operated group both cavernosal nerves were identified but not resected.…”
Section: Methodsmentioning
confidence: 99%
“…We have also observed that at the level of the pelvic ganglia, Sildenafil (SIL) exerts a neuroprotective effect by activating neurotrophic factors involved in neuronal survival and regeneration [26]. However, little is known of the role of NO/cyclic guanosine monophosphate (cGMP) pathways on cytokines and oxidative stress modulation after nerve resection in autonomic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These data parallel the growing body of evidence found in animal models, which indicate that smooth muscle (SM) apoptosis and NOS nerve fibre reduction with veno‐occlusive dysfunction may occur within 1–3 weeks after cavernous nerve neurotomy (Carrier et al ., ). The immediate chronic administration of PDE5Is in these animal models reduces anatomical alterations after cavernous nerve neurotomy (Schwartz et al ., ; Vignozzi et al ., , ; Kovanecz et al ., ,b; Sirad et al ., ; Hlaing et al ., ; Garcia et al ., ). In the only RCT assessing the effect of PDE5Is on the preservation of erectile tissue (Montorsi et al ., ), reduced shrinkage of penile length compared with placebo was observed upon low‐dose daily tadalafil administration.…”
Section: Discussionmentioning
confidence: 98%
“…The distal nerve shows overall distortion of normal nerve anatomy, axonal swelling and axonal vacuolization which are microanatomical signs of Wallerian degeneration [19]. Local conditions influence how initial regenerative axon sprouts emerge from parent axons [20], while CN injury triggers a cascade of events in PG neurons, including changes in expression of neurotransmitters, neurotrophic factors, cytokine production [21], and SHH pathway signaling [1112]. Following injury, the regenerative abilities of these important injured parasympathetic ganglion neurons and the factors in the environment that influence regeneration are poorly understood.…”
Section: Introductionmentioning
confidence: 99%